Uma querência entre acordes: práticas comunicacionais no peitaço da composição regional e a constituição de uma comunidade criativa - Lalis, Matheus Bernardes Paim (2023)
The present dissertation proposes an approach to the concept of Creative Community, relating it to the field of the Creative Industry, analyzing how communication contributes to the constitution of a community. The object of the study is the Peitaço da Composition Regional, a festival that was born out of a movement of women artists who come together with a view to creative production, and whose repercussions are directly manifested on the generation of intellectual property and on encouraging greater participation of women composers in gaucho regional music. The general objective of this study is to understand how communication can contribute to the constitution of a creative community in the Peitaço movement of Regional Composition. The specific objectives are: to bring the Creative Community concept to the Creative Industry area; map the phases of gaucho regional music and the insertion of women in this movement; identify how the environment created in the 1st Peitaço promotes creativity; to analyze the perceptions of Movimento Peitaço members about their role as a creative community. For that, a triangulation of methodological techniques was used from bibliographical research, documental and qualitative analysis, with the application of questionnaires and interviews based on the pragmatist approach stimulated by the problem and the research object, aiming at its understanding and possibilities as a communicative action. The results identified showed that the Peitaço da Composition Regional promotes a space that allowed women freedom and encouragement to compose, based on the bonds formed by the members through the use of communication, by sharing characteristics, causes and related objectives, which led to the feeling belonging to the movement. The study considers Peitaço a creative community that, through the use of creativity, seeks to solve a problem or issue common to the group - the scarce presence of women composers in Rio Grande do Sul music -, establishing communication as a contributor to the constitution of a community by establishing processes communication processes that result in the generation of products or processes resulting from creativity.